2014
DOI: 10.1007/s12032-014-0335-7
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of sorafenib plasma concentration by high-performance liquid chromatography in patients with advanced hepatocellular carcinoma: is it useful the application in clinical practice? A pilot study

Abstract: Pharmacokinetics and dose-finding studies on sorafenib were conducted on heterogeneous groups of patients with solid tumors. Portal hypertension, gut motility impairment and altered bile enterohepatic circulation may explain different sorafenib toxicological profile in cirrhotic patients. This study evaluated sorafenib plasma concentration in a homogeneous group of cirrhotic patients with hepatocellular carcinoma (HCC). Sorafenib concentrations were determined by liquid chromatography in 12 consecutive patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
27
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(32 citation statements)
references
References 22 publications
3
27
0
1
Order By: Relevance
“…Both compounds inhibited 195 cytopathic effects during infection and the viral replication ( Figure 4B, C, D, S5, and S6). Overall, five compounds, inhibiting downstream signaling of GFRs, prevented SARS-CoV-2 replication at clinically achievable concentrations ( Figure 4B and 5) (Eskens et al, 2001;Fucile et al, 2014;Martinez-Garcia et al, 2012;Munster et al, 2016;Sarker et al, 2015), emphasizing the importance of GFR signaling during SARS-CoV-2 infection and revealing clinically available 200 treatment options as drug candidates for COVID-19.…”
Section: Inhibition Of Growth Factor Signaling Prevents Viral Replicamentioning
confidence: 96%
“…Both compounds inhibited 195 cytopathic effects during infection and the viral replication ( Figure 4B, C, D, S5, and S6). Overall, five compounds, inhibiting downstream signaling of GFRs, prevented SARS-CoV-2 replication at clinically achievable concentrations ( Figure 4B and 5) (Eskens et al, 2001;Fucile et al, 2014;Martinez-Garcia et al, 2012;Munster et al, 2016;Sarker et al, 2015), emphasizing the importance of GFR signaling during SARS-CoV-2 infection and revealing clinically available 200 treatment options as drug candidates for COVID-19.…”
Section: Inhibition Of Growth Factor Signaling Prevents Viral Replicamentioning
confidence: 96%
“…Sorafenib suppresses the serine/threonine kinase subtypes of Raf, which are well known to regulate the Raf/MEK/ERK signaling pathway and inhibit tyrosine kinase receptors, including VEGFR2, PDGFR and IGFR. For this reason, sorafenib inhibits angiogenesis and tumor growth (52). Sorafenib has demonstrable preclinical and clinical activity against certain types of cancer (for example, HCC, and ovarian, breast and pancreatic cancer).…”
Section: Targeting Rafmentioning
confidence: 99%
“…The high degree of interindividual pharmacokinetic variability observed with sorafenib has important toxicological ramifications. For example, it was recently demonstrated that levels of sorafenib in plasma are correlated with the incidence of skin rash, with dose reduction and study withdrawal due to adverse effects, and with the development of severe adverse reactions …”
mentioning
confidence: 99%